Analysis of fruit thinning effect and underlying mechanism using metamitron on ‘Gala’ apples - Chen, Ru; Nie, Peixian; Wang, Laiping; Wang, Guiping; Zhang, Chunxiang; Zhao, Xianyan; Xue, Xiaomin (Frontiers in Plant Science, 2025)
To address the problems of artificial apple thinning, which are time-consuming, labor-intensive, and inefficient, this study examined the fruit thinning effect and mechanism of spraying metamitron at the young fruit stage on Gala apples grown on dwarfing inter-stocks. The results showed that spraying 500mg·L-1metamitron twice, at 3 mm and 9 mm fruit diameters, significantly reduced the fruit setting rate of inflorescences and flowers, thereby increasing the single fruit ratio. The photosynthetic parameter (Pn) and chlorophyll fluorescence parameters (Fv/Fm, ΦPSII, qP, and NPQ) were significantly inhibited by the treatment, resulting in a noticeable decrease in soluble sugar content. The treatment significantly increased abscisic acid (ABA) content and decreased the (Z+GA3+IAA)/ABA ratio. These results suggest that metamitron effectively thins apple fruit, with its mechanism likely related to damage to the leaf PSII reaction center structure, obstruction of photosynthetic electron transfer, insufficient soluble carbohydrate supply due to reduced photosynthetic rate, increased ABA content, and decreased auxin hormone/ABA ratio.